Does the risk of sperm competition help explain cooperation between reproductive competitors? A study in the ocellated wrasse (Symphodus ocellatus). - Stiver, Kelly A; Alonzo, Suzanne H (The American naturalist, 2013)
Although cooperating individuals may gain benefits, they risk being cheated by their allies. Therefore, to understand the persistence of cooperation by mutual benefits, it is important to document both the potential benefits of cooperation and the risks of cheating. We experimentally examined evidence of cooperation in the ocellated wrasse (Symphodus ocellatus), a fish species with males that exercise three reproductive strategies: satellite and sneaker males attempt to parasitically spawn in the nests of nesting males. Nesting males have been hypothesized to tolerate satellites as a result of satellite aid in defense against sneaker males and help in courting females. Here, we provide evidence that cooperation between reproductive competitors may arise in response to sperm competition from other males. After we experimentally removed satellites, nesting males had more sneakers at their nest and experienced a higher rate of sneaking when they spawned (increased sperm competition risk). When we experimentally distracted nesting males to prevent their acting aggressively toward satellites, satellites spawned with females and ate eggs in the nest. Our results suggest that nesting males and satellites gain fitness benefits of reduced direct reproductive and sperm competition through cooperation. However, nesting males risk losing paternity, while satellites experience increased aggression and must invest in aggression themselves (i.e., they act aggressively toward sneakers).
Keywords: *Competitive Behavior/ph [Physiology]; *Cooperative Behavior; *Perciformes/ph [Physiology]; *Sexual Behavior, Animal/ph [Physiology]; *Spermatozoa/ph [Physiology]; Aggression; Alternative male tactics; Analysis of Variance; Animals; Competition; Competitive Behavior; Cooperation; Cooperative Behavior; Female; Fertility; Fertility/ph [Physiology]; Male; Models, Biological; Nesting Behavior; Nesting Behavior/ph [Physiology]; Perciformes; Sexual Behavior, Animal; Sneak-fertilization; Sperm competition; Spermatozoa; aggression; analysis of variance; animal; article; biological model; competitive behavior; cooperation; cooperative breeding; dept.psy; female; fertility; male; nesting; peer-reviewed; perciform; persistence; physiology; reproductive strategy; sexual behavior; sneak copulation; sperm competition; spermatozoon